Pola Asuh Orang Tua pada Anak Broken Home - Burhanuddin, Hamam; Thohiroh, Muhaiminatut (Institut Agama Islam Sunan Giri Ponorogo, 2021)
Study aims to determine the parenting pattern of broken home children in Dander District, Bojonegoro Regency (1) What problems are faced by children related to Broken Home parenting, (2) How is the parenting pattern for Broken Home children, and (3) What factors support and hindering Broken Home parenting. This research is a type of field with a qualitative approach. The research subjects consisted of three broken home children with different backgrounds, namely divorced die and live divorced, and parents who are not present for a long time in full. The data analysis technique used is in the form of data reduction, data presentation, and verification of conclusion drawing. The result of this study is that it occurs in children from broken home families in terms of intellectual and child characteristics. Intellectually the problems that occur in the form of decreased cognitive abilities, reading delays, and difficulty concentrating during the teaching and learning process. While the characteristics that occur in children are having a bad temper, emotional instability, being sensitive, and having a closed personality. The parenting style applied is democratic parenting and permissive parenting. Factors that support and hinder parenting consist of internal factors and external factors. Internal factors include parental attention, parental religious understanding, and parental education. While external factors include the environment where the child lives.